Total Physical Response (TPR): Its Effect on Students’ Achievement in Reading Procedure Text: Total Physical Response (TPR): Pengaruhnya Terhadap Prestasi Belajar Siswa Dalam Membaca Teks Prosedur - Zulpan, Zulpan (JEES (Journal of English Educators Society), 2018)
The objectives of this study are to find out whether there is any significant effect of Total Physical Response (TPR) method on students’ achievement reading procedure text to the tenth grade students in one of Indonesian state vocational schools. This study is designed by using experimental method. It aims to know the effect of TPR method on students’ achievement reading procedure text. In this research, the tenth Grade were the population consisting of 572 students. Then, the researcher applied cluster random sampling to get 2 classes which have 78 students. Then the data was collected by using instrument. The instrument used is multiple choices test in which is the test divided post test and pre test. It showed that the scores got by students in X variable is 70.26 in which categorized to the good category. Afterwards, the scores got by students in Y variable is 62.95 in which categorized to the enough category. It is found that the result shows the score of t test > t table (3.91> 2.00). It means that there was any significant effect of Total Physical Response (TPR) Method on students’ achievement reading procedure text.